ANALISIS YURIDIS NORMATIF TINDAK PIDANA MEREK SEBAGAI KEJAHATAN TERHADAP HAK KEKAYAAN INTELEKTUAL - Andree Washington Hasiholan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
This study examines trademark crimes as a form of crime against Intellectual Property Rights (IPR) in the Indonesian legal system. As brands increase their role in global and national trade, violations such as counterfeiting and unauthorized use of trademarks have become serious threats not only to brand owners, but also to consumers and the stability of healthy business competition. The main focus of this analysis is on the application of the principle of lex specialis derogat legi generalis, where Law Number 20 of 2016 concerning Trademarks and Geographical Indications (MIG Law) applies as a special law that overrides general criminal provisions in the Criminal Code (KUHP). This study uses a normative legal research method with a literature study approach to analyze how the MIG Law constructs a legal concept that expressly classifies trademark violations as crimes against IPR. The analysis shows that the MIG Law not only provides more severe and specific sanctions than the Criminal Code, but also reflects a shift in the legal paradigm that views IPR as a vital economic asset requiring strong and separate criminal protection. This regulation is a manifestation of the law’s function as a means of social control and social engineering to foster a culture of respect for creativity and innovation in society. Ultimately, it is concluded that the criminalization of trademark infringement in the MIG Law is a strategic legal policy step to provide legal certainty, justice, and economic benefits for all stakeholders.